2022
DOI: 10.1159/000528116
|View full text |Cite
|
Sign up to set email alerts
|

Smartwatch ECG Tracing and Ischemic Heart Disease: ACS Watch Study

Abstract: BACKGROUND Smartwatches have become a widely used tool for health self-care. Its role in ischemic heart disease (IHD) has not been assessed. OBJETCIVES To evaluate the usefulness of smartwatch ECG registry in IHD. METHODS We present an observational study of 25 consecutive patients with acute IHD. Conventional ECG and smartwatch tracing were obtained simultaneously at admission. Waves of conventional and smartwatch ECGs were objectively compared. A survey on medical attitude was conducted among 12 physicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In this context, our research team recently executed a pilot study (ACS WATCH I) to assess the practicality of smartwatch recordings in select cases. The findings indicated that electrocardiographic recordings garnered through smartwatches hold potential as dependable aids for directing therapeutic interventions in Ischemic Heart Disease [6]. Nevertheless, a comprehensive validation study is imperative, given the limited scope of this pilot investigation.…”
Section: Introductionmentioning
confidence: 97%
“…In this context, our research team recently executed a pilot study (ACS WATCH I) to assess the practicality of smartwatch recordings in select cases. The findings indicated that electrocardiographic recordings garnered through smartwatches hold potential as dependable aids for directing therapeutic interventions in Ischemic Heart Disease [6]. Nevertheless, a comprehensive validation study is imperative, given the limited scope of this pilot investigation.…”
Section: Introductionmentioning
confidence: 97%
“…Nowadays, smartwatches offer much more than simply connecting to a mobile phone and managing basic functions. Recent studies have shown that, thanks to integrated sensors, smartwatches can monitor heart rate, ECG, and blood pressure, or measure peripheral blood oxygen saturation (SpO 2 ) values [1][2][3][4]. The advantage of real-time monitoring of vital signs using smartwatches is their convenient placement on the forearm, which does not restrict the user in daily activities compared to conventional blood pressure cuffs or finger sensors for SpO 2 measurement.…”
Section: Introductionmentioning
confidence: 99%